The Impact of Electronic Media on Patients with Inflammatory Bowel Disease - Cury DB; Paez LEF; Micheletti AC; Reis ST (Dove Medical Press, 2021)
Dídia B Cury,1,2 Loyná E Flores Paez,1 Ana C Micheletti,3 Sabrina T Reis4 1Inflammatory Bowel Disease Center, Scope Clinic, Campo Grande, MS, Brazil; 2Center for Crohn’s and Colitis, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA; 3Institute of Chemistry, Federal University of Mato Grosso do Sul, Campo Grande, MS, Brazil; 4Laboratory of Medical Investigation 55 (LIM55) – Urology Department, University of São Paulo Medical School, São Paulo, SP, BrazilCorrespondence: Dídia B CuryInflammatory Bowel Disease Center, Scope Clinic, Maracaju Street 1148, Campo Grande, MS, 79002-212, BrazilTel +55 67 3325 6040Email didiacury@gmail.comIntroduction and Objectives: Patients with chronic illnesses, such as inflammatory bowel disease (IBD), may often consult the internet, which can cause anguish, fear, stress and anxiety. The aim of our study is to evaluate the use of the internet and its effects on patients with IBD.Patients and Methods: This is a descriptive, cross-sectional study with quantitative frequency analysis. We applied a questionnaire comprising questions about internet use, and the DASS21 questionnaire to analyze internet impact on patients’ stress and/or anxiety for 36 months.Results: A total of 104 patients were included over a period of 45 days (82% CD, 18% UC). The mean age was 41.3 years (± 15.9 years). Internet use was more frequent in patients with a mean age of 39.5 years (± 14.4 years), with the highest frequencies found in the age group of 26– 36 years. Internet use were related to: 72.6% general information about the disease, 87.3% symptom information (42.1% once a week, 27.4% never, 18.8% once a month, 10.5% daily, and 3.2% twice a day). The most visited search engine was Google 63.7% and the most visited sites were: patient group sites 16.7%, health sites 16.2% medical sites 12.8%.Conclusion: The internet is often a resource utilized by patients with IBD and although these patients sought to obtain more information about their disease and their symptoms. The internet was not a factor influencing anxiety and stress for these patients.Keywords: inflammatory bowel disease, electronic media, internet, Brazil